PENGARUH BIMBINGAN SCAFFOLDING TERHADAP KETERAMPILAN PROSES SAINS DALAM PEMBELAJARAN KIMIA HIJAU - Sefia Muslikah; Muhammad Haris Effendi Hsb; Febbry Romundza (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2025)
This study aimed to investigate the effect of scaffolding guidance on improving science process skills of 10th grade students in green chemistry learning. The research employed a mixed-method approach with a quasi-experimental time series design involving 36 students at SMA Negeri 2 Muaro Jambi. Scaffolding techniques were implemented progressively through four stages: explaining, prompting, cueing, and questioning across four meetings. Data were collected through observation sheets, pretest-posttest assessments, and interviews. Results showed significant improvement in students' science process skills, particularly in measuring and communicating results. Statistical analysis using dependent t-tests revealed significant differences (p < 0.05) across all meetings. Effect size calculations showed large effects (Cohen's d > 0.8) for all scaffolding techniques. The cueing technique demonstrated highest effectiveness for measuring skills (t = -10.023), while questioning was most effective for communication skills (t = -9.791). This research contributes to science education by demonstrating that progressive scaffolding guidance can effectively enhance students' science process skills in chemistry learning contexts.